Проблемы Вавилонского города II тыс. до н.э. (По материалам Ура) - Дьяконов, И. M. (1973)
Diakonoff, I. M.; Problems of the Babylonian city in the second Millennium B.C. (Based on materials from Ur); engl. Résumé S. 211-225.